2006
DOI: 10.1097/00129492-200604000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Meniere's Disease: Prevalence of Contralateral Ear Involvement

Abstract: Most otologists are aware of the potential for contralateral ear involvement and conversion from cochlear hydrops to Meniere's disease after diagnosis. These changes are significant, require long-term follow-up for detection, and may necessitate further treatment. Patients should be counseled regarding this potential when interventions are considered, especially with respect to ablative treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
4
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 32 publications
6
77
4
2
Order By: Relevance
“…Another risk is that the treatment prescribed to control vertigo secondarily affects hearing in patients with severe hearing loss in the contralateral ear. In other published research papers, the probability of bilateral involvement has been estimated to range between 2 and 78% [House et al, 2006], which means that there is a great difference in the estimations and, above all, in the duration of the follow-up. This has important clinical implications for both advising the patient and planning treatment.…”
Section: Bilateralitymentioning
confidence: 96%
“…Another risk is that the treatment prescribed to control vertigo secondarily affects hearing in patients with severe hearing loss in the contralateral ear. In other published research papers, the probability of bilateral involvement has been estimated to range between 2 and 78% [House et al, 2006], which means that there is a great difference in the estimations and, above all, in the duration of the follow-up. This has important clinical implications for both advising the patient and planning treatment.…”
Section: Bilateralitymentioning
confidence: 96%
“…Epidemiological studies have shown that some patients with unilateral Meniere's disease progress to bilateral disease several years after the initial disease onset [18,19] . Furthermore, some studies have reported histological abnormalities in the contralateral ear in clinically diagnosed unilateral Meniere's disease [17,20] .…”
Section: Discussionmentioning
confidence: 99%
“…16,[32][33][34] House et al determinam uma prevalência de casos de DMB de 24%, sendo o aparecimento simultâneo em ambos os ouvidos em 11% dos casos e, em 14% dos casos, um aparecimento progressivo. 35 Num estudo a decorrer no nosso serviço, analisado pela última vez no final de 2015, numa amostra de 151 casos identificados com DM, segundo os critérios da AAO-HNS (1995), encontramos uma percentagem de casos de DMB de 12,6%.…”
Section: Idade De Aparecimento Dos Sintomas E Idade De Diagnósticounclassified
“…35 Paparella e Griebie reportam que 50% dos casos de DMB têm iní-cio de envolvimento do ouvido contralateral durante os primeiros dois anos após o início do aparecimento dos sintomas. Dos restantes, 27% têm início nos primeiros cinco anos e os remanescentes 23% até um intervalo máximo de 25 anos.…”
Section: Tempo De Envolvimento Do Ouvido Contralateralunclassified